Jejak Spiritualitas Calonarang dalam Dunia Digital sebagai Media Edukasi Agama Hindu - I Dewa Bagus Pinatih; I Ketut Putu Suardana; Rieka Yulita Widaswara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to explore how the TikTok account Calonarang Taksu implements communication strategies to deliver Hindu religious educational content, and to assess the extent to which these contents effectively enhance the audience’s understanding and spiritual awareness. A qualitative approach using content analysis was employed to examine three purposively selected videos, each with over one million views during the period of January to March 2024. Data were gathered through direct observation and digital documentation, and analyzed using the Uses and Gratifications theoretical framework. The findings indicate that the account conveys educational messages through religious visual symbols, performance dramatization, the use of local languages, and the depiction of sacred moments in Balinese Hindu rituals. The content addresses five dimensions of audience needs: informational, emotional entertainment, personal identity, social connection, and emotional expression. Overall, the content not only entertains but also strengthens cultural identity, fosters spiritual reflection, and facilitates meaningful religious experiences in digital spaces. Therefore, TikTok can be regarded as a potential platform for contextually transforming the delivery of religious teachings in the digital era.